2016
DOI: 10.1016/j.solmat.2016.03.018
|View full text |Cite
|
Sign up to set email alerts
|

Impact of the selenisation temperature on the structural and optical properties of CZTSe absorbers

Abstract: We present structural and optical spectroscopy studies of thin films of Cu2ZnSnSe4 (CZTSe) with strong copper deficiency deposited on Mo/Glass substrates and selenised at 450, 500 or 550 °C. Solar cells fabricated from these films demonstrated efficiencies up to 7.4% for selenisation at 500 °C. Structural analysis based on X-ray diffraction and Raman spectroscopy revealed the presence of SnSe2 in the film selenised at 450 °C but not detected in the films selenised at higher temperatures. A progressive decrease… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
23
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 28 publications
(24 citation statements)
references
References 52 publications
1
23
0
Order By: Relevance
“…As in the film the P2 band quenches by 70 K. At temperatures above 200 K the solar cell spectra show a broad band at 0.9 eV. Such bands, observed earlier in CZTS [28] and CZTSe [20,23,24], were attributed to band-to-band (BB) transitions, involving the recombination of free electrons from the conduction band with free holes from the valence band. The P3 band in the PL spectra of the solar cell gradually quenches with raising temperature however it retains a relatively high intensity up to temperatures of 300 K. High concentrations of charged defects generate tails in the density of states (DOS) of the conduction and valence bands of semiconductors.…”
Section: Resultsmentioning
confidence: 80%
See 2 more Smart Citations
“…As in the film the P2 band quenches by 70 K. At temperatures above 200 K the solar cell spectra show a broad band at 0.9 eV. Such bands, observed earlier in CZTS [28] and CZTSe [20,23,24], were attributed to band-to-band (BB) transitions, involving the recombination of free electrons from the conduction band with free holes from the valence band. The P3 band in the PL spectra of the solar cell gradually quenches with raising temperature however it retains a relatively high intensity up to temperatures of 300 K. High concentrations of charged defects generate tails in the density of states (DOS) of the conduction and valence bands of semiconductors.…”
Section: Resultsmentioning
confidence: 80%
“…The rate of this shift (j-shift) is 14 meV per decade of laser power change for the CZTSe/Mo film and decreases to 13 meV/decade for the cell spectra as shown in Table 1. The characteristic asymmetric shape of the P1 band, the invariance of this shape on the excitation intensity and the significant j-shifts suggest that the radiative recombination mechanism of this band is associated with band tails generated by spatial potential fluctuations due to high concentrations of charged defects [18,20,[23][24][25][26][27]. The P3 band in the PL spectra of the cell also increases its intensity at higher excitation.…”
Section: Resultsmentioning
confidence: 96%
See 1 more Smart Citation
“…The hypothesis of SnSe 2 formation due to a low supply of thermal energy during annealing is supported by observations performed in other works. Márquez et al observed a strong formation of SnSe 2 when processing CZTSe at 450°C that disappeared for samples processed at 500°C . The duration of the annealing was the same at both temperatures so the energy supplied to the sample was directly related to the annealing temperature.…”
Section: Discussionmentioning
confidence: 99%
“…47,[69][70][71] when processing CZTSe at 450°C that disappeared for samples processed at 500°C. 75 The duration of the annealing was the same at both temperatures so the energy supplied to the sample was directly related to the annealing temperature. What is more, Temgoua et al fabricated CZTSSe devices at 600°C for different annealing times and observed the formation of SnSe 2 from 1-to 30-minute annealings that vanished for longer annealing times.…”
Section: Discussionmentioning
confidence: 99%